Pravilo podjetniške presoje in odškodninska odgovornost članov uprave banke - Podgorelec, Peter (Podjetje in delo, 2015)
The article discusses the business judgement rule and civil liability of members of banks% management boards. The business judgement rule constitutes a presumption that members of the board exercise due diligence in their conduct subject to certain conditions (business decision, good faith, acting without conflict of interests, acting on an informed basis and acting in the best interest of the company). Even though the rule may also be invoked by members of banks% boards, the banking sector is provided with a significantly narrower margin of discretion as laid down by the regulation itself, which is attributable to specific banking regulation requirements and restrictions, pertaining to the management of various types of risks in particular.
Keywords: bančništvo; banke; člani; management; odgovornost; odškodninska odgovornost; uprava; upravljanje; vodenje